2019
DOI: 10.1136/bcr-2018-227233
|View full text |Cite
|
Sign up to set email alerts
|

Multiple basal cell carcinomas in a patient with myotonic dystrophy type 1

Abstract: A man in his early 60s with myotonic dystrophy type 1 (DM1) and an extensive history of non-melanoma skin cancer presented with multiple pearly, erythematous papules on his face, head, trunk and extremities, clinically consistent with basal cell carcinoma (BCC). Due to the numerous BCC and history of multiple and early-onset BCC, examination was concerning for a hereditary BCC syndrome. Subsequent histopathology confirmed BCC. Genetic testing was negative for basal cell nevus syndrome and clinical findings wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Nevertheless, further studies are required to fully elucidate EGFR activity in DM1, because altered EGFR signaling is associated with human cancers [48]. Several publications have indexed the overall risk of cancers in DM1 patients [4,49], with the most prevalent being skin cancers, specifically basal cell carcinoma [50,51]. To that end, we cannot exclude endocytic pathway alterations from the mechanism underlying the onset of cancers and/or metabolic diseases [52] in DM1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, further studies are required to fully elucidate EGFR activity in DM1, because altered EGFR signaling is associated with human cancers [48]. Several publications have indexed the overall risk of cancers in DM1 patients [4,49], with the most prevalent being skin cancers, specifically basal cell carcinoma [50,51]. To that end, we cannot exclude endocytic pathway alterations from the mechanism underlying the onset of cancers and/or metabolic diseases [52] in DM1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…39 Since then, 9 case reports have been published on DM1 patients presenting with multiple BCC suggesting an association between the repeat-expansion disorder and BCC. 40 A UK retrospective study on 1061 DM1 patients and 15,119 DM1-free matched individuals in the UK Clinical Practice Research Datalink demonstrated an increased risk of all skin cancers in DM1 patients compared to their matched DM1-free controls, with the highest risk for BCC (hazard ratio, 5.78; 95% CI, 3.36-9.92; P < .0001). 41 DM1 patients also demonstrated an approximately 2-fold increase in melanoma risk, though not statistically significant.…”
Section: Skin Cancer and Myotonic Dystrophymentioning
confidence: 99%